2022
DOI: 10.3390/ijms23031822
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons Enhance the Repair of Ultraviolet Radiation-Induced DNA Damage and Regulate Cutaneous Immune Suppression

Abstract: Type I interferons (IFNs) are important enhancers of immune responses which are downregulated in human cancers, including skin cancer. Solar ultraviolet (UV) B radiation is a proven environmental carcinogen, and its exposure contributes to the high prevalence of skin cancer. The carcinogenic effects of UV light can be attributed to the formation of cyclobutane pyrimidine dimers (CPD) and errors in the repair and replication of DNA. Treatment with a single dose of UVB (100 mJ/cm2) upregulated IFNα and IFNβ in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…These therapeutic results derive from IFN1α’s anti-proliferative and anti-angiogenic effects within RCC tissue, as well as its modulatory cellular differentiation activity via growth factor cross-talk and transcriptional control over key cellular differentiation genes [ 59 , 60 ]. Interestingly, in a very recent murine model investigation, IFN 1α/β demonstrated a novel genomic photo-damage repair activity via NER gene induction and a protective effect against UVR-induced immuno-suppression [ 61 ]. Taking into account the findings of our current study, it may be the case that TDs have constituted an occult molecular therapeutic target in metastatic RCCs undergoing immunomodulatory cytokine treatment via IFN 1α-induced improvements in NER capabilities in TD-positive renal/RCC tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These therapeutic results derive from IFN1α’s anti-proliferative and anti-angiogenic effects within RCC tissue, as well as its modulatory cellular differentiation activity via growth factor cross-talk and transcriptional control over key cellular differentiation genes [ 59 , 60 ]. Interestingly, in a very recent murine model investigation, IFN 1α/β demonstrated a novel genomic photo-damage repair activity via NER gene induction and a protective effect against UVR-induced immuno-suppression [ 61 ]. Taking into account the findings of our current study, it may be the case that TDs have constituted an occult molecular therapeutic target in metastatic RCCs undergoing immunomodulatory cytokine treatment via IFN 1α-induced improvements in NER capabilities in TD-positive renal/RCC tissue.…”
Section: Discussionmentioning
confidence: 99%
“…First, the rate of skin cancer in autoimmune photosensitive diseases is not comparable to those with DNA repair deficiencies, indicating no persistence of increased nuclear DNA damage( 58 ). Second, type I IFN may increase repair of cyclobutane pyrimidine dimers, the main nuclear DNA lesion upon UV light exposure( 59 ). Third, mtDNA is more susceptible to oxidative modifications due to close proximity to ROS production, a lack of protective histones and insufficient DNA repair mechanisms compared to nuclear DNA( 19, 22, 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, molecules with antioxidant and inhibitory properties against TD formation, such as α-tocopherol (vitamin E) [ 73 ], isoflavone genistein [ 74 ], and resveratrol [ 75 ], may have potential applications in RCC prevention. Interestingly, a recent study using a murine model revealed IFN 1α/β to have a protective effect against UV-induced immunosuppression, and to enhance genomic photo-damage repair activity via NER gene induction [ 76 ]. Considering the current findings, TDs might have been overlooked as molecular therapeutic targets in metastatic RCCs treated with IFN 1α, by improving NER capabilities in TD-positive renal/RCC tissue.…”
Section: Discussionmentioning
confidence: 99%